PERILAKU PETANI ANGGOTA PERKUMPULAN PETANI PEMAKAI AIR (P3A) RUKUN SANTOSO DI DESA KONAROM BARAT KECAMATAN DUMOGA TENGGARA - Suseno .; Theodora M. Katiandagho; Wilson M. Wangke (AGRI-SOSIOEKONOMI, 2015)
The aim of research is to describe the Rukun Santoso water user associations (P3A) Konarom West Village, District Southeast Dumoga and analyze behaviour of its members. The collection of data was carried out for five months, from January until May 2015. The primary data collected through face to face interviews. Respondents was selected for 30 respondents by using random sampling mechanism. The interviews was conducted based on questionnaires that have prepared before. The secondary data was obtained through agencies that related to this research topic. The data analysis is descriptive. The results showed that knowledge of water user farmer groups in the organization is very good and then supported by the attitude of members of water user farmers is positive in favor of any program that is planned and the action of water user farmer association is good enough so that each program can run as expected.Keywords: knowledge, attitude, action, Rukun Santoso, Southeast Dumoga